ARCHAISMS IN THE ENGLISH LANGUAGE - Abdurahmonova Hayitgul; Egamberdiyeva Hadicha (TADQIQOTLAR, 2026)
Introduction Language is constantly changing and evolving. Over time, new words are created, while some old words gradually disappear from everyday use. These outdated or old-fashioned words are called archaisms. Archaisms play an important role in understanding the historical development of language and literature. They allow linguists, students, and researchers to study how language has evolved over centuries. Although archaisms are rarely used in modern everyday speech, they still appear in literature, religious texts, historical writing, and poetry. Understanding archaisms helps learners appreciate classical works and understand the cultural background of earlier periods. Language is constantly changing and evolving. Over time, new words are created, while some old words gradually disappear from everyday use. These outdated or old-fashioned words are called archaisms. Archaisms play an important role in understanding the historical development of language and literature. They allow linguists, students, and researchers to study how language has evolved over centuries. Although archaisms are rarely used in modern everyday speech, they still appear in literature, religious texts, historical writing, and poetry. Understanding archaisms helps learners appreciate classical works and understand the cultural background of earlier periods.